THE ROLE OF WOMEN FARMERS IN ADVANCING SUSTAINABLE DEVELOPMENT GOALS (SDGS) TO PROMOTE WELFARE IN LABUHAN BATU REGENCY - Dhea Nita Syafina Rambe; Syaad Afifuddin; Raina Linda Sari (RADJA PUBLIKA, 2026)
This study investigates the role of women farmers in advancing Sustainable Development Goals (SDGs) to improve household welfare in Labuhan Batu Regency. Women farmers are central contributors to agricultural production, yet their involvement is often constrained by limited access to resources, health challenges, and institutional barriers. This study employs a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with 100 respondents selected through the Slovin formula. The findings show that women farmers’ role and health have a positive and significant effect on welfare, while access to resources does not directly influence welfare. However, an SDG-based economy significantly improves welfare and acts as an effective mediator for the roles, health, and resource access of women farmers. The mediating effect indicates that sustainable economic mechanisms strengthen the contribution of women farmers toward welfare improvement. The study concludes that enhancing women’s participation, improving health access, and optimizing resource utilization within an SDG-aligned economic framework are essential strategies for increasing household welfare. These results provide empirical support for integrating gender-responsive and sustainability-based approaches into regional agricultural development policies.